2021
DOI: 10.1001/jama.2021.19415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra-articular Platelet-Rich Plasma vs Placebo Injection on Pain and Medial Tibial Cartilage Volume in Patients With Knee Osteoarthritis

Abstract: IMPORTANCE Most clinical guidelines do not recommend platelet-rich plasma (PRP) for knee osteoarthritis (OA) because of lack of high-quality evidence on efficacy for symptoms and joint structure, but the guidelines emphasize the need for rigorous studies. Despite this, use of PRP in knee OA is increasing.OBJECTIVE To evaluate the effects of intra-articular PRP injections on symptoms and joint structure in patients with symptomatic mild to moderate radiographic medial knee OA.DESIGN, SETTING, AND PARTICIPANTS T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
188
5
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(200 citation statements)
references
References 37 publications
4
188
5
3
Order By: Relevance
“…PRP is a concentrate of plasma and platelets. It is widely used in many musculoskeletal indications, although limited evidence supports its ability to improve symptoms effectively [45][46][47]. Regarding nerves, animal models provide evidence for peripheral nerve injuries but the evidence in compression neuropathy is limited.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…PRP is a concentrate of plasma and platelets. It is widely used in many musculoskeletal indications, although limited evidence supports its ability to improve symptoms effectively [45][46][47]. Regarding nerves, animal models provide evidence for peripheral nerve injuries but the evidence in compression neuropathy is limited.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Is platelet-rich plasma a solution looking for a problem? This small randomised trial of 288 people over 50 years old with radiographic evidence of mild to moderate knee osteoarthritis found that three weekly joint injections of platelet-rich plasma (versus placebo) resulted in no significant difference in knee pain scores or tibial cartilage volume (a measure of disease progression) over 12 months 3. Joint injection, whether with saline or platelet-rich plasma, reduced pain scores by 32-37%.…”
Section: Platelet-rich Plasma For Knee Osteoarthritis: Disappointing Resultsmentioning
confidence: 99%
“…The best outcomes were attained by individuals aged 51-65 years, with lower mechanical axis angle, and by patients with K/L stage 2 OA [38]. However, the study by Bennell et al showed that among patients with symptomatic mild-to-moderate radiographic knee OA, intra-articular injection of PRP did not result in a significant difference in symptoms at 12 months compared with saline injection (placebo) [39].…”
Section: Discussionmentioning
confidence: 98%
“…Patients with symptomatic mild-to-moderate radiographic knee OA who had intra-articular injections of PRP were not found to have improved symptoms or joint structure at 12 months. Therefore, the authors did not support use of intra-articular injections of PRP for the treatment of knee OA [39].…”
Section: Randomized Controlled Trialsmentioning
confidence: 98%
See 1 more Smart Citation